Struktur Dan Fungsi Mantra Tradisi Nyapih di Desa Karangwotan Kecamatan Pucakwangi Kabupaten Pati - Ale Sandya Rindi Amida; Yuli Kurniati Werdiningsih; Sunarya (Kawruh: Journal of Language Education, Literature and Local Culture, 2024)
Menyapih is the process of separating the child from breast milk or the cessation of a mother's breastfeeding. The purpose of this study is to describe in depth the structure and function of the nyapih mantra. Along with the development of the increasingly advanced times, the current generation forgets that they must still maintain the culture that exists in society. Similarly, the mantra of the nyapih tradition now feels foreign to the community. This is because the tradition has rarely been carried out and few people want to learn it. Thus, there is an urge to do research on the nyapih mantra. This research focuses on the structure and function of spells. This research method uses a qualitative method. This research uses the theory of spell structure and spell function from Heru Saputra. This study produced findings on the structure of the spell contained in the nyapih mantra, namely, the title reflects the purpose of the spell, which is to separate the child from breast milk. The opening element contains a request for blessings and a request for guidance and protection to a figure who has higher power. The purpose element in this mantra contains wishes and hopes. The suggestive element in this mantra is related to the existence of God stating that all the purposes of the mantra can be fulfilled with the permission of Allah. The concluding element reflects the belief in the community of the mantra-user, as well as the expression of individuals and societies in their beliefs and hopes in Almighty God. This research also results in the function of the spell nyapih, which is individual and social. The mantra is individual, this mantra is a medium for individuals to express hopes, beliefs, and maintain connectivity with traditions and cultures that have been inherited. The nyapih mantra is social in nature, this tradition reflects the cultural identity, religious beliefs and livelihoods of the community.